An International Reference Reagent for the detection of anti‐human neutrophil antigen‐1a. Issue 2 (23rd September 2012) - Metcalfe, P.; Rigsby, P.; Pearson, H.; Lucas, G.
<x xml:space="preserve">Abstract</x> Background and Objectives Testing for neutrophil antibodies has become more common as awareness of transfusion‐related acute lung injury (TRALI) has increased. However, unlike other areas of blood cell antibody testing, there are no certified reference reagents available with which laboratories can determine the sensitivity of detection of their assays. This report describes the production and evaluation of a freeze‐dried preparation of human plasma, code 09/284, containing anti‐human neutrophil antigen‐1a (anti‐HNA‐1a) for use as a minimum sensitivity reagent. Materials and Methods One‐millilitre of aliquots of plasma containing anti‐HNA‐1a were freeze‐dried in glass ampoules. To characterize the material, 24 laboratories took part in an international collaborative study. The participants evaluated doubling dilutions of the material using their in‐house routine assays and recorded the highest dilution in which the antibody could be detected. Results When diluted 1 in 4, most laboratories were able to detect the anti‐HNA‐1a in the material, and the participants agreed that this was an appropriate level to set as the minimum sensitivity required. Conclusions In October 2011, the WHO Expert Committee on Biological Standardization approved the material 09/284 as an International Reference Reagent for the detection of anti‐HNA‐1a.